Improving Energy Efficiency of OFDM Using Adaptive Precision Reconfigurable FFT - Abdoli, Hatam; Nikmehr, Hooman; Movahedinia, Naser; de Dinechin, Florent (Circuits, systems, and signal processing, 2017)
Being an essential issue in digital systems, especially battery-powered devices, energy efficiency has been the subject of intensive research. In this research, a multi-precision FFT module with dynamic run-time reconfigurability is proposed to trade off accuracy with the energy efficiency of OFDM in an SDR-based architecture. To support variable-size FFT, a reconfigurable memory-based architecture is investigated. It is revealed that the radix-4 FFT has the minimum computational complexity in this architecture. Regarding implementation constraints such as fixed-width memory, a noise model is exploited to statistically analyze the proposed architecture. The required FFT word-lengths for different criteria—namely BER, modulation scheme, FFT size, and SNR—are computed analytically and confirmed by simulations in AWGN and Rayleigh fading channels. At run-time, the most energy-efficient word-length is chosen and the FFT is reconfigured until the required application-specific BER is met. Evaluations show that the implementation area and the number of memory accesses are reduced. The results obtained from synthesizing basic operators of the proposed design on an FPGA show energy consumption experienced a saving of over 80 %.